The Biology and Evolution of Calcite and Aragonite Mineralization in Octocorallia - Conci, Nicola; Vargas, Sergio; Wörheide, Gert (Frontiers in Ecology and Evolution, 2021)
Octocorallia (class Anthozoa, phylum Cnidaria) is a group of calcifying corals displaying a wide diversity of mineral skeletons. This includes skeletal structures composed of different calcium carbonate polymorphs (aragonite and calcite). This represents a unique feature among anthozoans, as scleractinian corals (subclass Hexacorallia), main reef builders and focus of biomineralization research, are all characterized by an aragonite exoskeleton. From an evolutionary perspective, the presence of aragonitic skeletons in Octocorallia is puzzling as it is observed in very few species and has apparently originated during a Calcite sea (i.e. time interval characterized by calcite-inducing seawater conditions). Despite this, octocorals have been systematically overlooked in biomineralization studies. Here we review what is known about octocoral biomineralization, focusing on the evolutionary and biological processes that underlie calcite and aragonite formation. Although differences in research focus between octocorals and scleractinians are often mentioned, we highlight how strong variability also exists between different octocoral groups. Different main aspects of octocoral biomineralization have been in fact almost entirely studied in the (calcitic) gorgonian Leptogorgia virgulata and/or the precious coral Corallium rubrum. These include descriptions of calcifying cells (scleroblasts), calcium transport and chemistry of the calcification fluids. With the exception of few histological observations, no information on these features is available for aragonitic octocorals. Availability of sequencing data is also heterogeneous between groups, with no transcriptome or genome available, for instance, for the clade Calcaxonia. Although calcite represents by far the most common polymorph deposited by octocorals, we argue that studying aragonite-forming could provide insight on octocoral, and more generally anthozoan, biomineralization. First and foremost it would allow to compare calcification processes between octocoral groups, highlighting homologies and differences. Secondly, similarities (external exoskeleton) between Heliopora and scleractinian skeletons, would provide further insight on which biomineralization features are driven by skeleton characteristics (shared by scleractinians and aragonitic octocorals) and those driven by taxonomy (shared by octocorals regardless of skeleton polymorph). Including the diversity of anthozoan mineralization strategies into biomineralization studies remains thus essential to comprehensively study how skeletons form and evolved within this ecologically important group of marine animals.